Evaluating impacts of desulfurization and depolymerization on thermodynamics properties of crumb rubber modified asphalt through molecular dynamics simulation. (14th March 2022) - Jiao, Bozong; Pan, Baofeng; Che, Tiankai
Highlights: CRMA models with different crumb rubber degradation levels were constructed. The effects of degradation on thermodynamics properties of CRMA were investigated. The degradation could promote the compatibility between crumb rubber and asphalt. The diffusions of CRMA were more sensitive to degradation at high temperatures. Abstract: In this study, the thermodynamics properties of crumb rubber modified asphalt (CRMA) were evaluated using molecular dynamics (MD) simulations. CRMA models with different crumb rubber degradation (desulfurization and depolymerization) degrees were constructed and verified through the thermodynamics parameters. Then the effects of desulfurization and depolymerization behaviors as well as temperature field on thermodynamics properties were investigated. For the CRMA, its compatibility, interfacial properties, diffusion behaviors and volumetric properties were analyzed by a series of methods, involving solubility parameter, binding energy, mean square displacement and fractional free volume. The results showed that both the crumb rubber desulfurization and depolymerization could promote the compatibility between crumb rubber and asphalt, with crumb rubber desulfurization contributing more to the improvement of compatibility. In addition, it was discovered that desulfurization and slight depolymerization of crumb rubber increased the interfacial performance between CR and asphalt, while the excessive depolymerization for crumb rubber showed the opposite effects. Furthermore, increasing the temperature could reduce the binding energy when the temperature was over 373 k. Moreover, the diffusion behaviors of CRMA were more sensitive to the crumb rubber degradation degree at high temperatures. The diffusion coefficients of CRMA at high temperatures showed a more obvious increase with the degradation of crumb rubber than those at low temperatures. Finally, the FFV was not suitable for evaluating the effects of crumb rubber degradation on the volumetric properties of CRMA that both the temperature increasing and probe radius decreasing improved the FFV of CRMA, while it did not show an obvious trend with the variation of crumb rubber degradation degree.